A survey of plant bacterial diseases of nanded district - Gawate, A B; Papdiwal, P B (Current Botany, 2011)
During the survey of bacterial diseases of trees of Nanded district, 9 diseases were observed. Majority of them were observed on fruit trees. The diseases observed were Leaf spot of Butea monosperma, , Ficus benghalensis and Termenalia catappa; Angular leaf spot of Ficus religiosa, black spot of Mangifera indica and Punica granatum; leaf necrosis of Annona squamosa and Psidium guajava; and Citrus canker of Citrus aurantifolia. A brief report of this investigation is presented in this paper.